Communication Apprehension among Students of Bangladesh: A Comparative Study between Online and Offline Classes - Razib, Mehedy Hassan; Pinky, Farzana Tasnim; Al-Zobayer, MD. (South Asian Journal of Social Sciences and Humanities, 2022)
This research study looks at students’ communication apprehension (CA) in online and offline classes. We wanted to comprehend whether their concern has changed about CA during online classes or not. In this quantitative research, we completed two surveys that asked them demographic questions. Four hundred and ninety-nine (499) students of public universities took part in online classes in August 2021 by completing the Personal Report of Communication Apprehension (PRCA-24). Another survey was conducted on 438 students during the offline classes in February 2022. We then analyzed the data in SPSS. The PRCA-24 scores of students in both studies determine that most of the students have high communication apprehension. They suffer from general anxiety, do not want to involve in any discussion during class, and have less self-esteem. It has been found that students’ fears of communication in academic settings negatively affect their learning and performance. This study can be useful in communication disorder discipline to find out where is the actual problem to communicate. This study will pave the way for further research on what steps can be taken to overcome the problem of fear in communication or whether any changes in teaching methods can be made.